Effectiveness of Using the Independent Curriculum Based Problem Based Learning Model in Learning Trigonometry Material in Class X State High School 8 Manado - Andra Christine Tombokan; James U. L. Mangobi; Jorry Ferry Monoarfa (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2024)
The objective of this study is to assess the efficacy of employing the Problem-Based Learning approach in the acquisition of Trigonometry concepts. This study examines four metrics of learning efficacy: student learning outcomes, student engagement during the learning process, student feedback on learning, and the teacher's aptitude in facilitating learning. This research falls under the category of quantitative descriptive research. The research was conducted at SMA Negeri 8 Manado during the odd semester of the 2023/2024 academic year. The study included a sample of 38 students from class X-I. The employed data collection approaches include testing, observation, and administering questionnaires. The study determined that the utilization of the Problem-Based Learning (PBL) approach in teaching Trigonometry content yielded positive results. This is exemplified by the attainment of the four metrics that measure the efficacy of utilizing the learning model: (1) Student learning results in the subject matter are classified as thoroughly comprehensive. (2) Student activities during the learning process are classified as satisfactory. (3) Students exhibit a favorable attitude towards the learning process. (4) The teacher's aptitude for overseeing the learning process is exceptional.